Pengaruh Pendekatan Steam Melalui Media Loose Parts Dalam Mengembangkan Kemampuan Numerasi - Putri, Putri Andriani; Yuniarti, Yuniarti; Sudarti, Sudarti (Jurnal Kajian Anak (J-Sanak), 2025)
The use of instructional media plays a crucial role in the teaching and learning process. Loose parts media function as educational tools that facilitate teachers in developing children's numeracy skills and support the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach, which effectively stimulates these abilities. This study aims to enhance the numeracy skills of children aged 5–6 years through the implementation of the STEAM approach using loose parts media. The research employed an experimental method with a quantitative approach and utilized a saturated sampling technique. The sample consisted of 10 children enrolled at Aletheia Christian Kindergarten in Pontianak, comprising 8 boys and 2 girls. Data were collected through observation, interviews, and testing, using a one-group pretest-posttest design (Pre-Experimental Design). Data analysis was conducted using a paired sample t-test with SPSS version 27, which revealed a t-value of -31.432 and a significance level of Sig. (2-tailed) = 0.001 at α = 0.05 with degrees of freedom (df) = 9. Based on these results, the alternative hypothesis (Ha) was accepted while the null hypothesis (H0) was rejected, indicating that the STEAM approach utilizing loose parts media had a statistically significant effect on the development of children's numeracy skills. Therefore, loose parts media can be considered an effective instructional tool for improving numeracy skills in early childhood education